(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to define media economics and its impact on social development in Libya, to reveal the true state of the Libyan economy and the most prominent future challenges facing media development within it, and to outline the role and procedures for achieving this development in the future through media promotion. The study reached a number of important conclusions, particularly regarding the role of Libyan media in promoting economic development. Financial, administrative, technical, and technological challenges continue to hinder development in the Libyan media economy, due to the overemphasis on economic and technological aspects, weak cooperation in the field, and the absence of specialized media outlets and media professionals with expertise in economic matters.